Inter-Basin Water Transfers: Balancing Water Scarcity Solutions with Environmental and Socio-Economic Impacts from Nepalese Perspective - Khatri, Kumar; Gurung, Smriti (Pragyaratna प्रज्ञारत्न, 2024)
Inter-basin water transfer (IBWT) involves moving water across drainage divides to address water scarcity, support agriculture, industry, recreation, and generate hydropower. While practiced since ancient times, modern IBWTs gained momentum in the 19th century and have since expanded globally. These projects range from small-scale transfers to large water transfer megaprojects (WTMPs). IBWTs can help mitigate water shortages, enhance food and energy security, and support ecosystem restoration, but also pose risks such as habitat degradation, biodiversity loss, and socio-economic disruptions. Though Nepal has practiced IBWT since the 17th century, the complex environmental and socio-economic consequences observed globally have yet to be fully assessed in the country. Furthermore, a number of IBWTs in the country are in pipeline. Therefore, this review is an attempt to shed light on different aspects of IBWTs including a brief historical perspective; the scale; and to evaluate the environmental and; socio-economic impacts globally and describe the scenario and associated implications in Nepalese context. This study selected articles based on IBTWs, their relevance to environmental impacts, socio-economic effects, and the role of IBWTs. Sources include peer-reviewed journals, government reports, and case studies, focusing on global examples and specific challenges in Nepal. The major findings of this study is that IBWTs are gaining popularity and are becoming important in water-food-energy nexus despite their environmental and socio-economic implications. However, if such projects are undertaken with comprehensive environmental assessments, sustainable water management practices, with inclusive policy frameworks, countries can leverage IBWT projects to meet their growing demands for water, energy, and food, while safeguarding ecological integrity and community welfare.